Kualitas Pelayanan Publik Dalam Pembuatan e-KTP di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Langkat - Sri Yunita Br Sitepu; Adam Adam; Warjio Warjio (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study aims to analyze the quality of public services in creating e-KTP at the Population and Civil Registration Office (Disdukcapil) of Lalat Regency. The analysis was carried out based on Zeithaml's theory, which includes five service quality dimensions: tangible, reliability, responsiveness, empathy, and assurance. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation of Disdukcapil officers and the community as service recipients. The study results show that the e-KTP-making service in Langkat Regency still faces obstacles, such as limited facilities and technological infrastructure, system disruptions that affect service reliability, long waiting times, and suboptimal responsiveness. In addition, attention to vulnerable groups is still inadequate. However, data security guarantees and transparent procedures have increased public trust. To improve the quality of service, it is recommended that infrastructure be improved, the number and training of officers increased, information technology systems optimized, and wider procedures socialized. This effort is expected to increase the efficiency and transparency of population administration in Lalat Regency.